The integrator project in a higher course in Gastronomy using Information and Communication Technologies - Firmino, Lucas Fabricio de Souza (Universidade Federal do Rio de Janeiro, 2023)
This study seeks to analyze the proposals of Integrator Project in a college course of Culinary Arts, as an active methodology that stimulates the development of teamwork by the students. As it is an open and distance learning (ODL), encouraging interdisciplinarity among students during the course is always a necessity. Each Integrator Project was planned seeking to make academics carry outvisits, research and practical activities outside the academic environment, however, due to the COVID-19 pandemic, it was necessary to make even greater use of Information and Communication Technologies (ICTs)  so that the activities could be developed by the academics during the course.